PEMBERIAN ASAP CAIR DARI JERAMI PADI DALAM PENGOLAHAN CAKALANG (Katsuwonus pelamis) PRESTO ASAP - Fidel Ticoalu; Hetty Ondang; Nova Tumanduk; Dolfie Dj Kaligis; Palehel Mulalinda; Fernando Wowiling (Politeknik Kelautan dan Perikanan Bitung, 2019)
This rice straw waste contains high levels of hemicellulose, cellulsoa and lignin. Cellulose content is high enough so that the rice waste has the potential as a base for making liquid smoke. One of the uses of liquid smoke is in fish products. The treatment that will be carried out in this study is based on the way the liquid smoke concentration is given to the product, the duration of cooking pressure and the method of liquid smoke. The treatment is: Liquid Smoke Concentration (A), A1: 0.8%, A2: 1.2%, Duration of Presto (B), B1: 60 Minutes, B2: 90 Minutes, B3: 120 Minutes, Method of Giving Liquid Smoke (C), C1: Soaked in Liquid Smoke for 5 minutes then dippedo and then dried at 150 ° C for 30 minutes, C2: Dipresto then soaked in Liquid Smoke for 5 minutes then dried at 150 ° C for 30 minutes, C3: Dipresto in Smoke The liquid is then dried at 150 ° C for 30 minutes. Based on the results of the research obtained, it can be concluded that: Rice Straw can be used as a material for making liquid smoke, Cakalang fish dipresto with liquid smoke using rice straw as the main raw material for skipjack tuna for all treatments, has good quality. Variations in testing of variations in treatment combinations, showed varying differences in each combination of treatments and there was no fixed combination of treatments to describe one test. Hedonic testing, the treatment that shows good results is at a concentration of 1.2%, presto time 90 minutes using either dipresto method or soaked first. In testing the trio duo, the treatment that showed good results was at a concentration of 0.8%, presto time 60 and 90 minutes was also good with the method of either dipresto first or soaked first.